Fikrah Rusydi Ahmad Th’aimah wa Mahmud Kamil al-Naqah fi Ta’lim al-Lughah al-‘Arabiyyah ‘Inda Dhu’i al-Madkhal al-Itthishal - Munir, Moh. (Arabiyatuna: Jurnal Bahasa Arab, 2022)
This article is written to find out and analyze Rusydi Ahmad Thu’aimah’s and Mahmud Kamil An-Naqah’s thoughts on teaching the Arabic language using a communication approach. This article is written resting upon a library research and a content analysis approach. The findings indicate that: 1) There are four kinds of learning elements according to Rusydi Ahmad Thu’aimah and Mahmud Kamil An-Naqah. They are messages, the sender, the receiver, and learning media. 2) There are three kinds of learning strategies according to Rusydi Ahmad Thu’aimah and Mahmud Kamil An-Naqah. They are metacognitive strategy, cognitive strategy, and sosio-affective strategy. 3) There are two kinds of problems in learning the Arabic language using the communication approach according to Rusydi Ahmad Thu’aimah and Mahmud Kamil An-Naqah. They are a) the problem in the same language, which is divided into sound, vocabulary, word, sentence, and writing; and b) the problem of external language, which is divided into the educational materials, the teacher, and the learning media.